ANALISIS TINGKAT PERPUTARAN PERSEDIAAN, TINGKAT PERPUTARAN PIUTANG, TINGKAT PERPUTARAN MODAL KERJA DAN TINGKAT PERPUTARAN KAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR KIMIA DI BURSA EFEK INDONESIA 2010-2012 - Mulatsih Mulatsih (Jurnal Ilmiah Ekonomi Bisnis, 2015)
This research aims to analyze the author made whether there is influence receivables turnover, inventory turnover, and turnover of working capital and cash flows of the level of profitability of the chemical sector companies listed in Indonesia Stock Exchange in 2010-2012. The data used in this research is secondary data, financial statement data in the form of balance sheet and income statement. The items are used, among others, receivables, inventory, working capital, cash, sales, and cost of goods sold. The method of analysis used to test the hypothesis in this research is multiple linear regression analysis, t test, F test and R Square. The results of this study are the level of accounts receivable turnover, inventory turnover and working capital turnover rate simultaneously and partial effect on the profitability of the company. Keywords: accounts receivable, inventory, working capital, cash, profitability